Resistant to change? The transition to parenthood among married adults in China. Issue 2 (9th February 2017) - Tong, Yuying; Piotrowski, Martin; Zhang, Yueyun
Abstract : Using retrospective life history data from the 2008 Chinese General Social Survey (CGSS) and discrete time event history analysis, this study investigates the transition to parenthood of adult males and females for the 1965 to 2004 marriage cohorts. We find that Chinese people generally prefer to become parents soon after marriage. We also find that more recent marriage cohorts are less likely to become parents compared to earlier cohort for males, but this is not the case for women. This indicates that economic or role incompatibility in general does not prevent women from becoming mothers, which in general supports the idea that there are alternative resources available for women to balance the role incompatibility in China's context. The extended family is an important resource for married couples to rely upon to raise young children. This study sheds light on China's family therapy practice, which should take into consideration the demographic trends and cultural factors in understanding the role conflict within the family, such as intergenerational relations and gender ideology. Practitioner points: Role incompatibility of having children can be relieved by extended family, so therapy programmes dealing with intergenerational relationship should be developed Family therapists should consider the pace of gender ideology change in child rearing during negotiation of the husband‐wife relationship Training programmes can be more specific to the extended family for dealing with child rearing skills and potential conflict resolutions.